COOPERATION IN THE CONTEXT OF PUBLIC ADMINISTRATION: METHODOLOGICAL ASPECT - Myroshnychenko , A. (Theory and Practice of Public Administration, 2021)
The trend of growth in the modern world of scale and number of problems and contradictions of a social nature, unfortunately, takes place in Ukraine in particular. Therefore, it is time to find adequate ways for the state to overcome a number of socio-economic problems. At the same time, with the further spread of the idea of public administration and the efforts of our state to move to a qualitatively new level of public administration through reforms, which, admittedly, are not always systemic, more and more attention is drawn to such a participant in public administration as civil society. It is in this context that the author proposes to look at such a rather new phenomenon as cooperation and its formalized manifestation - cooperative. To this end, the author presents the positions of the pioneers of cooperative thought and analyzes some existing approaches of modern scientists to the definition of such concepts as “cooperation” and “cooperative”, which shows that cooperation, first and foremost, scientists understand as a process of cooperation. Also common is the scientific position that a cooperative is considered a collection of cooperatives and their associations. However, there is a clear lack of unity among scholars in their views on the essence and content of such a concept as “cooperation”, and hence the concept of “cooperative”. The author emphasizes that cooperation has great potential in terms of its participation in the process of public administration, because as a component of civil society it can formulate certain collective interests, articulate pressing problems of society and participate in the process of public policy and its subsequent process implementation, while assuming part of the burden of implementing decisions. Along with this, cooperation is able to give some feedback to the state, a real assessment of the results of the latter, and this is no less important.